A Review of Universal Fashion (Journal of Fiber Bioengineering and Informatics, 2023)
This paper summarizes universal fashion for the physically disabled, visually disabled, mentally disabled and the elderly. From both physical and psychological needs, it focuses on clothing materials, clothing structure and smart wearable devices. Through this review, it is concluded that there are two distinctive features of the research on universal fashion. The first is the uneven focus on different universal groups. The largest research has been done on universal fashion for people with physical disabilities and it is the most mature. There are fewer studies on universal fashion for people with mental disabilities, and there are large research gaps. Secondly, the focus on universal fashion for the same group of people is also uneven. There is more research on clothing patterns than on clothing materials, but the development and application of clothing materials are more important, and there are still gaps in this part. Research on universal fashion for children with autism has not focused on the urgent need to address the problem of getting lost, so the author has designed an anti-wandering vest for children with autism, and it is worthwhile to continue to study this part in depth in the future. The future direction of research into universal fashion can be divided into two areas. On the one hand, there is the strengthening of new materials (including clothing fabrics and smart fibers) for universal people. On the other hand is the rational transfer of research methods from established disciplines to universal fashion research, relying on new technologies and interdisciplinary exchanges.